2016
DOI: 10.4172/2161-1041.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-Medicine in Gene(s) Targeting Future Direction for Sickle Cell Disease Management

Abstract: Sickle cell disease (SCD) is a genetic disease of hemoglobin (Hb) that occurs due to a non-conservative substitution of a polar glutamate (Glu) by non-polar valine (Val) in an invariant region, of hemoglobin β chain-subunit. This change distorts the normal Hb folding resulting in a sticky patch on the surface of the β-chains and associated complications. Nigeria has the largest burden of SCD globally with an estimated 150,000 new born affected annually.This review is aimed at analyzing the phytomedicines use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…Study on Cajanus cajan seed shows that Ciklavit® contains phenylalanine, carjaminose, and hydroxybenzoic acid as active constituents and are thought to be the reason for its anti-sickling effect. 19 Study also found that flavonoids such as morin and silymarin inhibit Pgp ATPase activity by inhibiting azidopine binding to P-gp. The findings of this study indicate a potential for significant flavonoid-drug interactions with P-gp substrates.…”
Section: Impact Of Ciklavit® On Proguanil Pharmacokinetic Urinary Datamentioning
confidence: 89%
“…Study on Cajanus cajan seed shows that Ciklavit® contains phenylalanine, carjaminose, and hydroxybenzoic acid as active constituents and are thought to be the reason for its anti-sickling effect. 19 Study also found that flavonoids such as morin and silymarin inhibit Pgp ATPase activity by inhibiting azidopine binding to P-gp. The findings of this study indicate a potential for significant flavonoid-drug interactions with P-gp substrates.…”
Section: Impact Of Ciklavit® On Proguanil Pharmacokinetic Urinary Datamentioning
confidence: 89%
“…3 HbF, however, has been found to have a higher affinity for oxygen than all other variants of Hb. 4 In adults, very small quantities of HbF (<2%) have been detected in the blood. Researchers found that SCD patients in Saudi Arabia and India that had high levels of HbF, even as adults, had milder anaemic episodes.…”
Section: Induction Of Fetal Haemoglobinmentioning
confidence: 99%
“…In West African for example, historical and scientific records have described different names used to qualify SCD children among the three main Nigerian tribes. The Yorubas, constituting the dominant population in the west called them “abiku” translated “sufferers'' or “children that bring sadness” [ 10 , 11 ], the Ibos called them “Ogbanje” [ 12 ], and the Hausas called them “Sankara-miji” [ 13 ]. It is the major innate disorder in Nigeria, affecting about 4 million population at prevalence of 2% at birth while more than 40 million persons have sickle cell traits.…”
Section: Introductionmentioning
confidence: 99%